Cowpea Curculio, Chalcodermus aeneus Boheman (Insecta: Coleoptera: Curculionidae) - John L. Capinera (EDIS)
This document provides an in-depth profile of the cowpea curculio, Chalcodermus aeneus Boheman, focusing on its distribution, life cycle, host plants, damage caused, natural enemies, and management strategies. The cowpea curculio primarily affects legumes in the southeastern United States, with significant damage to cowpea crops. The article details the insect's biology, including its overwintering habits, egg-laying process, larval development, and pupation. It also discusses various control methods, including insecticides, cultural practices, and biological control, highlighting the challenges in managing this pest effectively. Published: August 2001.